2021
DOI: 10.1371/journal.pone.0246385
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of seasonal influenza vaccination in postpartum women, Honduras

Abstract: Background Influenza during pregnancy may cause serious neonatal outcomes including stillbirth, fetal distress, preterm birth, congenital abnormalities, and stunted growth. Pregnant women are the highest priority group for seasonal influenza vaccination, but low coverage has been repeatedly reported in this population. Understanding reasons for and for not receiving the seasonal influenza vaccine is needed to design communication strategies to increase vaccination coverage. This study aimed to describe knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Direct physician recommendations have been shown to be associated with seasonal influenza vaccination among risk groups, including pregnant women [ 31 ], older adults [ 32 ], and individuals with comorbidities [ 33 ]. One systematic review found that pregnant women who received recommendations from healthcare providers were 20 to 100 times more likely to be vaccinated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct physician recommendations have been shown to be associated with seasonal influenza vaccination among risk groups, including pregnant women [ 31 ], older adults [ 32 ], and individuals with comorbidities [ 33 ]. One systematic review found that pregnant women who received recommendations from healthcare providers were 20 to 100 times more likely to be vaccinated [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Flood et al found that perception of susceptibility to influenza was associated with vaccine hesitancy for children [ 18 ]. Madewell et al found that perceived benefits for mother and infant, and easy accessibility of vaccines were the most cited reasons for influenza vaccination in Honduras [ 32 ]. Mills et al reported that the most common response of parents refusing vaccination was a fear of long-term complications for their children due to vaccines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%